2014
DOI: 10.18052/www.scipress.com/ilcpa.38.111
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Heat Transfer in a Rectangular Channel with Mounted Obstacle

Abstract: The fully-incompressible, viscous and stationary Navier-Stokes equations are solved for the laminar flow over an obstacle placed on the lower of a channel. The Reynolds number is varied from 100 to 400. In all cases studied the flow field proves to be steady. Several distinct flow features are identified: a horseshoe vortex system, inward bending flow at the side walls of the obstacle, a horizontal vortex at the downstream lower-half of the obstacle and a downstream wake containing two counter-rotating vortice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…They reported that the individual rectangular modules caused a larger enhancement in the heat transfer inside the channel in comparison to the square modules. The results of other studies have provided evidence that, as the space between obstacles is decreased, the fluid flow in the channel is consequently enhanced, and that an increase in the Reynolds number (Re) enhances the process of heat removal around the obstacles, chiefly around the obstacle corners [2][3][4]. In a numerical study, Mohamed Toumi et al [5] investigated the three-dimensional shearing flows of Newtonian fluids around a cuboid obstacle.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the individual rectangular modules caused a larger enhancement in the heat transfer inside the channel in comparison to the square modules. The results of other studies have provided evidence that, as the space between obstacles is decreased, the fluid flow in the channel is consequently enhanced, and that an increase in the Reynolds number (Re) enhances the process of heat removal around the obstacles, chiefly around the obstacle corners [2][3][4]. In a numerical study, Mohamed Toumi et al [5] investigated the three-dimensional shearing flows of Newtonian fluids around a cuboid obstacle.…”
Section: Introductionmentioning
confidence: 99%
“…Parndtl number affects the precise location of the periodically fully developed region. Gareh [11] carried out numerical investigation of heat transfer in a rectangular channel with mounted obstacle. He showed that as the value of the Reynolds number increases, the heat removed from the obstacles increases sensibly with a maximum heat removal around the obstacle corners.…”
Section: Introductionmentioning
confidence: 99%